2017
DOI: 10.21533/pen.v5i2.125
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Air Permeability Property of Air-Laid Nonwoven Fabrics Using Regression Analyses

Abstract: Air-laid nonwoven fabrics are generally used for hygienic care products such as diaper, adult nappy and sanitary napkins. Air permeability is one of the foremost properties that affect the usage performance of these hygienic care products. In this study, 10 different air-laid nonwoven fabric samples are produced. The porosity ratios of these samples are determined by digital image processing methods. Air permeability of the samples is tested by digital air permeability test device. Then regression analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As other fabric properties such as fabric count, weight, thermal resistance, and evaporative resistance are mutually dependent on thickness and/or air permeability, it has been hypothesized that the selected two fabric properties can properly represent the linear regression with performance. Different studies used linear regression analysis to find out the relation between fabric properties and performance [ 49 , 50 ]. For the statistical analysis, the mentioned fabric properties in Table 1 were considered as independent variables (input) and the amount of moisture and air gap size were the ordinal independent parameters.…”
Section: Methodsmentioning
confidence: 99%
“…As other fabric properties such as fabric count, weight, thermal resistance, and evaporative resistance are mutually dependent on thickness and/or air permeability, it has been hypothesized that the selected two fabric properties can properly represent the linear regression with performance. Different studies used linear regression analysis to find out the relation between fabric properties and performance [ 49 , 50 ]. For the statistical analysis, the mentioned fabric properties in Table 1 were considered as independent variables (input) and the amount of moisture and air gap size were the ordinal independent parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Table (8) shows that model ( 3) is an acceptable tool to predict fabric stiffness from proposed factors that affecting fabric pattern because all values of error are closed to (0) that indicate to a high performance of prediction model. Table (9) displays that model ( 3) is the best model of prediction performance by applying regression analysis to predict fabric stiffness. It gets high percentage of explanation between fabric factors and fabric stiffness that means higher values of R-Squared (0.939) and (MSE = 1.06E-05).…”
Section: Modelmentioning
confidence: 99%
“…In addition, Çelik, H. İ. [9] depended on image processing to get porosity ratios of air-laid nonwoven fabric samples. The research tried to obtain numerical value of porosity based on applying image processing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that these fabric properties can represent linear regression with tensile strength. Different studies were found where linear regression analysis was used to model the relation between fabric properties and performance [43,44].…”
Section: Analyzing the Experimental Datamentioning
confidence: 99%